Analisis Peningkatan Hasil Belajar Termodinamika Melalui model Problem Based Learning Berbantuan PhET Simulation - Surya Paola Dinata; paola, surya (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Physics learning on thermodynamics topics is often considered difficult due to its abstract concepts and the need for strong visualization. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model assisted by PhET Simulation in improving students’ learning outcomes compared to conventional instruction. The research was conducted at SMK Negeri 9 Muaro Jambi and involved two classes: a control class that learned through the lecture method and an experimental class that received PBL instruction supported by PhET Simulation. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics and N-Gain analysis. The results show that the control class experienced a moderate improvement with an N-Gain value of 0.52, while the experimental class demonstrated a high improvement with an N-Gain value of 0.72. These findings indicate that the implementation of PBL assisted by PhET Simulation is more effective in helping students develop a deeper understanding of thermodynamics concepts. The implications of this study highlight that integrating problem-based learning models with digital simulations can serve as a relevant and adaptive strategy to enhance the quality of physics learning in the classroom.